2006
DOI: 10.1111/j.1524-4725.2005.31903
|View full text |Cite
|
Sign up to set email alerts
|

Peritumoral Fibrosis in Basal Cell and Squamous Cell Carcinoma Mimicking Perineural Invasion: Potential Pitfall in Mohs Micrographic Surgery

Abstract: BACKGROUND. Perineural invasion (PI) in cutaneous basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) is linked to an aggressive course. We describe a histologic mimic for PI that we termed peritumoral fibrosis (PF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 28 publications
(38 reference statements)
1
32
0
Order By: Relevance
“…Benign inclusions in the perineural space simulating PNI and nodular peritumoral Wbrosis as a mimicker of PNI must be considered in the diVerential diagnosis of PNI (Fellegara and Kuhn 2007;Hassanein et al 2005). But, additional immunohistochemical staining, e.g., for p16 and S-100 protein, might help to overcome any diYculties in the majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Benign inclusions in the perineural space simulating PNI and nodular peritumoral Wbrosis as a mimicker of PNI must be considered in the diVerential diagnosis of PNI (Fellegara and Kuhn 2007;Hassanein et al 2005). But, additional immunohistochemical staining, e.g., for p16 and S-100 protein, might help to overcome any diYculties in the majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…21 The diagnosis of PNInv in cSCC may be complicated by a number of factors. Histologic findings may mimic or mask PNInv, including peritumoral fibrosis 35,36 and re-excision perineural proliferation, 36 among others. Excessive tissue manipulation or asymmetric tumor spread along the nerve sheath may create ''skip'' areas on sectioning that result in false-negative surgical margins.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that rates of PNI are higher in cSCCs of the head and neck (H&N) compared to other anatomic sites which may confound past reports (Chang et al, 2004). Comparisons of PNI incidence are complicated by multiple factors that include the challenges associated with detection of PNI using hematoxylin and eosin (H&E) staining (obscured nerve and morphologically imperceptible tumor cells), lack of a standardized histological definition of PNI (delineating true PNI from focal abutment secondary to impingement of nerve by tumor), differences in detection rates between cryostat and formalinfixed paraffin-embedded tissue sections (Mohs micrographic surgery vs traditional histopathologic examination), and histological mimics such as Renault bodies, perineural fibrosis, reactive neuroepithelial aggregates, and reparative perineural hyperplasia (Campoli et al, 2014;Dunn, Morgan, Beer, Chen, & Acker, 2009;Hassanein et al, 2005;Kurtz, Hoffman, Zimmerman, & Robinson, 2005;Ronaghy, Yaar, Goldberg, Mahalingam, & Bhawan, 2010;Zhou, Xu, Zhang, Zhao, & Wu, 2014). Lastly, in select cutaneous and noncutaneous malignancies it has been shown that the use of immunohistochemistry (IHC) can aid in the detection of PNI, especially in the tumor bulk where nerve can be obscured by tumor (intratumoral PNI) (Berlingeri-Ramos, Detweiler, Wagner, & Kelly, 2015;Kurtz et al, 2005;Scanlon et al, 2014;Zhou et al, 2014).…”
Section: Incidence Of Pni In Cutaneous Malignanciesmentioning
confidence: 99%